Prediction of water stream flow in the context of climate change - Fauzan Hanisah, Zulhaimi (2016)
The increase in global surface temperature in response to the changing composition of the atmosphere will significantly impact upon local hydrological process and water sources. This situation will lead to the need for an assessment of regional climate change impacts. The application of Statistical Downscaling Model (SDSM) and Identification of Unit Hydrograph and Component Flows from Rainfall, Evaporation and Streamflow Data (IHACRES) were used as rainfall runoff models to stimulate streamflow event in Sungai Kecau, Kuala Lipis, Pahang catchment based on daily rainfall. The rainfall station is taken at Kampung Bandar at Ulu Kechau. The SDSM model is the derivation of National Centre for Environmental Prediction (NCEP) reanalysis data and observation of locally methodological variables that have been calibrated using large – scale predictors variables. The SDSM model validation has been done by independent period of NCEP reanalysis. The outcome obtained was used to generate the possible future scenarios of meteorological variables and then the input is used to the IHACRES model. Stimulation of corresponding future streamflow changes was stimulated by IHACRES model and the observed station data in the catchment Sungai Kecau, Kampung Dusun.